2008
DOI: 10.1080/10509670801992418
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Innovative Post-Arrest Diversion Program: 12-Month Recidivism Analysis

Abstract: We report the results of an evaluation study of a diversion program, operated by the Miami-Dade County Juvenile Assessment Center in Florida. The Post-Arrest Diversion (PAD) program represents an innovative approach to treatment and intervention within the juvenile justice system that utilizes standardized psychosocial risks and needs assessment to provide individual treatment for first-time, non-violent juvenile offenders. The present study evaluated the effectiveness of the PAD program with regard to one-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
(48 reference statements)
1
13
0
Order By: Relevance
“…While juveniles in diversion programs had significantly lower rates of recidivism than those in probation, the offenders who failed to complete actually had higher reoffense rates than the youth in probation. Similar patterns demonstrating the essential role of program completion have been reported in a postarrest diversion program (Dembo et al, 2008), a family empowerment intervention (Dembo et al, 2000), and a rural alcohol diversion program (Martire & Larney, 2011).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…While juveniles in diversion programs had significantly lower rates of recidivism than those in probation, the offenders who failed to complete actually had higher reoffense rates than the youth in probation. Similar patterns demonstrating the essential role of program completion have been reported in a postarrest diversion program (Dembo et al, 2008), a family empowerment intervention (Dembo et al, 2000), and a rural alcohol diversion program (Martire & Larney, 2011).…”
supporting
confidence: 64%
“…Many recent studies have similarly reported that juvenile diversion programs produced lower rates of recidivism (e.g., Dembo, RamirezGarcia, Rollie, Schmeidler, Livingston, & Hartsfield, 2000;Dembo, Walters, Wareham, Burgos, Schmeidler, Hoge, & Underwood, 2008;Schwalbe, Gearing, MacKenzie, Brewer, & Ibrahim, 2011;and Wilson & Hoge, 2013a). Research has found higher levels of youth functioning accruing from diversion programs (e.g., Gavozzi, Wasserman, Partridge, & Sheridan, 2000;Hodges et al, 2011;and Jordan et al, 2013).…”
mentioning
confidence: 98%
“…These discretionary programs have largely been established to reduce the likelihood of a defendant's future involvement with the criminal justice system and to offer defendants an alternative to traditional criminal conviction and punishment (Salzberg, 1983). One study tracked the recidivism of former participants of a Post-Arrest Diversion Program (PAD) for first time non-violent misdemeanor juvenile offenders in Miami-Dade County (Dembo et al, 2008). The study found that successful completion of PAD significantly reduced graduates' likelihood of re-arrest over 12 months, controlling for socio-demographic variables, the charge type at first arrest, and assessed recidivism risk level (Dembo et al, 2008).…”
Section: Deferred Prosecution Programsmentioning
confidence: 99%
“…One study tracked the recidivism of former participants of a Post-Arrest Diversion Program (PAD) for first time non-violent misdemeanor juvenile offenders in Miami-Dade County (Dembo et al, 2008). The study found that successful completion of PAD significantly reduced graduates' likelihood of re-arrest over 12 months, controlling for socio-demographic variables, the charge type at first arrest, and assessed recidivism risk level (Dembo et al, 2008). Similarly, a study of the Correct Course Diversion Program in the Wayne County Juvenile Justice system of Michigan found similar results, with just 7.7 % of program participants adjudicated for a new offense over a similar one-year follow-up period.…”
Section: Deferred Prosecution Programsmentioning
confidence: 99%
“…There is a great deal of rehabilitation and health promotion research for youth in detention, particularly on programs with objectives relating to preventing recidivism by reducing offending (e.g., Dembo et al, 2008;Eddy, Whaley, & Chamberlain, 2004) or increasing prosocial behaviors (e.g., Greenwood, 2008). Research on the sexual risk-taking behaviors of incarcerated women with HIV supports the use of TPB concepts to measure predictors of risky behaviors and to develop health interventions for detained populations (Hogben, St. Lawrence, Hennessy, & Eldridge, 2003).…”
mentioning
confidence: 99%